How to Persuade the Students to Read Complicated Texts: An Experience Drawn from the Use of Digital Technologies - V. V. Radaev (Moscow Polytechnic University, 2022)
With the inflow of the new generations of students, university teachers in social sciences and humanities have been challenged by a crisis of textual culture given the students tend to increasingly avoid reading complicated academic texts. In these circumstances, traditional arrangements of seminars and students' homework are becoming less effective. This paper is aimed at exploring the new capacities for coping with the new critical situation. We address the issue of why we should keep the practices of active reading and how examination of complicated academic texts contribute to the formation of the students' critical thinking. Both the special literature and personal teaching experience of the author are attracted. Traditional forms of teaching arrangements are analyzed. Then we use an experience of a digital platform to demonstrate the potential ways of resolving the teaching problems. They include active reading dealing with the reflexive work, interactive discussions in the class and in the virtual environment. We also show that additional efforts associated with the use of digital technologies pay back enabling the teacher to control the students' homework more effectively and provide a more adequate assessment of the educational outcomes.